Kepemimpinan Visioner sebagai Strategi Penanaman Karakter Anti Korupsi di Madrasah Ibtidaiyah - Noor Alfi Fajriyani (The Prime is under the provision of the Study Program of Islamic Elementary School Teacher Training (PGMI) of Sekolah Tinggi Ilmu Tarbiyah Aqidah Usymuni Sumenep Indonesia, 2025)
Corruption in Indonesia is still a hot problem, many efforts or efforts have been made by the government for this one case. The efforts made by the government have resulted in an increase, namely Indonesia managed to be ranked 102 out of 180 countries. The purpose of this study is to examine in depth and describe strategies for instilling anti-corruption character in elementary school-age students using visionary leadership styles. The research method used is a qualitative method with a case study approach conducted at the Ibtidaiyah Tarbiyatul Ulum Madrasah in Batu City. Data collection was carried out through observation techniques and in-depth interviews. Madrasa heads, teachers, and students were the main informants of the study. The collected data were checked for validity with triangulation techniques, then analyzed using Milles Huberman's analysis techniques. The results of this study show that the visionary leadership style is one of the strategies that supports efforts to cultivate an anti-corruption character. This leadership style encompasses four dimensions that can be used as a means of learning the character of anti-corruption, namely; Direction determinant, change agent, spokesperson, and suri tauladan (coach). These four dimensions are empowered as a means of strengthening the anti-corruption character to students.